Cooper-pair distribution function $$D_{cp}(ω ,T_c)$$ D cp ( ω , T c ) for superconducting $$\hbox {D}_3\hbox {S}$$ D 3 S and $$\hbox {H}_3\hbox {S}$$ H 3 S - G. I. González-Pedreros (Nature Portfolio, 2021)
Abstract Cooper-pair distribution function, $$D_{cp}(ω ,T_c)$$ D cp ( ω , T c ) , is a recent theoretical proposal that reveals information about the superconductor state through the determination of the spectral regions where Cooper pairs are formed. This is built from the well-established Eliashberg spectral function and phonon density of states, calculated by first-principles. From this function is possible to obtain the $$N_{cp}$$ N cp parameter, which is proportional to the total number of Cooper pairs formed at a critical temperature $$T_c$$ T c . Herein, we reported $$D_{cp}(ω ,T_c)$$ D cp ( ω , T c ) function of the compressed $$D_3S$$ D 3 S and $$H_3S$$ H 3 S high- $$T_c$$ T c conventional superconductors, including the effect of stable sulfur isotopes in $$H_3S$$ H 3 S . $$D_{cp}(ω ,T_c)$$ D cp ( ω , T c ) suggests that the vibration energy range of 10–70 meV is where the Cooper pairs are possible for these superconductors, pointing out the possible importance of the low-energy region on the electron–phonon superconductivity. This has been confirmed by the fact that a simple variation in the low-frequency region induced for the substitution of S atoms in $$H_3S$$ H 3 S by its stable isotopes can lead to important changes in $$T_c$$ T c . The results also show proportionality between $$N_{cp}$$ N cp parameter and experimental or theoretical $$T_c$$ T c values.